Continuity and Change
1 online resource
Keywords: Bringing together a multidisciplinary team of authors, this book relays the untold story of postwar migration between Ireland and Australia. Spanning the period 1945-2024, it explores the experiences of migrants from the Republic of Ireland and Northern Ireland and provides insights into the multiple reasons these migrants came to Australia, factors which prompted permanency or return, and the extent of continuity and change between recent arrivals and their historical predecessors.Contemporary flows are examined through the lens of social, economic, policy, and technological changes occurring at the time in Ireland, Australia, and globally. Decades of economic boom and bust in Ireland, including the growth and demise of the Celtic Tiger, the impact of government investment in education in the Republic, and the Troubles in Northern Ireland, occurred alongside marked changes in Australia's immigration policy. During this time, an increased affordability of international travel and communication brought new dynamics to the tyranny of distance that characterised historical flows. How contemporary migrants from Ireland navigated these changes in terms of identity and belonging, homesickness, and transnationalism are the key themes which are explored. The role of Ireland's Government in relation to its migrant community in Australia and the impact of COVID-19 are also considered.This book not only fills a gap in Ireland's diaspora research but also contributes to migration studies more broadly, particularly the experiences of invisible immigrants.